Global research progress of endothelial cells and ALI/ARDS: a bibliometric analysis - Zhou, Tong; Long, Kunlan; Chen, Jun; Zhi, Lijia; Zhou, Xiujuan; Gao, Peiyang (Frontiers in Physiology, 2024)
Background: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are severe respiratory conditions with complex pathogenesis, in which endothelial cells (ECs) play a key role. Despite numerous studies on ALI/ARDS and ECs, a bibliometric analysis focusing on the field is lacking. This study aims to fill this gap by employing bibliometric techniques, offering an overarching perspective on the current research landscape, major contributors, and emerging trends within the field of ALI/ARDS and ECs.Methods: Leveraging the Web of Science Core Collection (WoSCC) database, we conducted a comprehensive search for literature relevant to ALI/ARDS and ECs. Utilizing Python, VOSviewer, and CiteSpace, we performed a bibliometric analysis on the corpus of publications within this field.Results: This study analyzed 972 articles from 978 research institutions across 40 countries or regions, with a total of 5,277 authors contributing. These papers have been published in 323 different journals, spanning 62 distinct research areas. The first articles in this field were published in 2011, and there has been a general upward trend in annual publications since. The United States, Germany, and China are the principal contributors, with Joe G. N. Garcia from the University of Arizona identified as the leading authority in this field. American Journal of Physiology-Lung Cellular and Molecular Physiology has the highest publication count, while Frontiers in Immunology has been increasingly focusing on this field in recent years. "Cell Biology" stands as the most prolific research area within the field. Finally, this study identifies endothelial glycocalyx, oxidative stress, pyroptosis, TLRs, NF-κB, and NLRP3 as key terms representing research hotspots and emerging frontiers in this field.This bibliometric analysis provides a comprehensive overview of the research landscape surrounding ALI/ARDS and ECs. It reveals an increasing academic focus on ALI/ARDS This is a provisional file, not the final typeset article and ECs, particularly in the United States, Germany, and China. Our analysis also identifies several emerging trends and research hotspots, such as endothelial glycocalyx, oxidative stress, and pyroptosis, indicating directions for future research. The findings can guide scholars, clinicians, and policy-makers in targeting research gaps and setting priorities to advance the field.